THE ROLE OF FOREIGN ECONOMIC RELATIONS OF CHINA ON THE MODERN STAGE AND ITS IMPACT ON KAZAKHSTAN - Kondybaeva, S.; Sadykhanova, G. K.; Czerewacz-Filipowicz, Katarzyna; Li, Zengrong (Farabi Journal of Social Sciences, 2020)
The article is dedicated for analyses cooperation of China with world economy, because as statistics shows PRC has powerful position. In the article, important historical periods were analyzed, as these historical moments had significant influence on China’s economy formation after World War II. Nowadays, the growth of the global economy growing fast. For PRC one of the main features of economic growth is the foreign economic activity. In this regard, the cooperation with overseas countries and neighbor countries is the most sufficient task. Partnership between countries, especially in the trade form are effective for both sides, the reason is that countries have opportunities for rising economies. The model of acting foreign economic relations for China is economic zones. Such zones attract for partnership as create favorable conditions between countries. PRC’s economic zones concentrated on the territories with industrial structures and these areas are integrated with international relations. As history of Silk way shows, China is a country with rich experience in trading and nowadays world recognize PRC as a power in the world. This article analyzes the foreign economic activity of China. The article describes international relations as a crucial part of the transformation of the national economic system. The work considers literature review of the formation of the worldwide division of labor from the side of theory and methodology. On an example of China explains the development of the national economy with an excess of one of the factors. The article analysis a regression model of influence economic relationships between Kazakhstani and Chinese companies within in the context of the project "One Belt - One Way". Keywords: government policy, international relations, trade, regression model